Petrologia de granitos alcalinos com alto flúor mineralizados em metais raros: o exemplo do Albita-granito da mina Pitinga, Amazonas, Brasil - COSTI, Hilton Túlio (Universidade Federal do Pará, 2017)
The mineral deposits of the Pitinga mine are related to the Proterozoic Água Boa and Madeira granites. Both are intrusive in the 1888 ± 3 Ma old acid volcanic rocks of the lricoumé Group. The Madeira Granite is composed by four facies, which emplacement sequence was inferred from its field relationships. The early facies is an 1824 ± 2 Ma old, porphyritic, metaluminous amphibole biotite syenogranite, which locally shows rapakivi texture. This facies is followed by an 1822 ± 1 Ma old, equigranular, peraluminous alkali feldspar biotite gravite. The two late facies are an 1818 ± 2 Ma old porphyritic, hypersolvus, alkali feldspar grafite and subsolvus albite gravite. Contact relationships indicate that the liquids forming these two late phases coexisted during the magmatic stage. This implies that they were emplaced almost simultaneously and also that the albite gravite and the hypersolvus grafite have a similar age. The albite gravite is composed by two facies. The dominant is a gray, peralkaline core facies (CAbG), which is composed essentially by albite, quartz and K-feldspar, accompanied by cryolite, zircon, polylithionite, riebeckite, Li-Fe mica, cassiterite, pyrochlore and magnetite. The modal proportions of the essential phases are similar, suggesting a magmatic origin for the CAbG and a cotectic or near minimum composition for its melt. Other features indicating a magmatic origin for the CAbG are: (1) the common occurrence of microscopic snowball textures; (2) it's petrographic and geochemical homogeneous character; (3) local presence of associated rocks with fluidal or pegmatitic textures. The CAbG is transitional to a reddish, peraluminous border facies (BAbG), found along the contacts of the albite with the early facies of the Madeira Granite. The BAbG is composed by albite, quartz and K-feldspar, with subordinate amounts of fluorite, zircon, chlorite, cassiterite, hematite, and columbite. The BAbG modal proportions of the essential phases are more variable and it has higher quartz and lower albite modal contents compared with the CAbG. The BAbG was originated by the autometasomatic alteration of the CAbG. The fluids involved in this process had a strongly oxidizing character and associated chemical changes destabilized the peralkaline mineralogy of the CAbG as evidenced by the replacement of cryolite, micas, pyrochlore and riebeckite. EMPA analyses indicate that the feldspars of the CAbG have near end-member compositions. The K-feldspars (Or —98%) are not perthitic and show high contents of Rb20 (-2%) and Fe2O3 (-0.6%), while the albites (Ab —99%) show anomalously high Fe2O3 (-1%) and relatively low Al2O3. These compositional characteristics indicate: a final crystallization temperature around 500°C or lower for the CAbG; the Al2O3 depleted character of the CAbG melt. Two micas were identified in the CAbG, both showing extremely low K/Rb ratios and high contents of Fe, Zn e Li. The more abundant is a Zn-Rb-polylithionite and the other is dark, Fe-Li mica with high Zn, F and Rb contents. The latter is relatively impoverished in Al2O3 and has Fe in tetrahedral positions, being tentatively classified as a tetra-ferri-Li mica. The unusual chemical compositions of micas and feldspars, as weli as the associated Sn, Nb, Zr, F, mineralization indicate that the CAbG derived from a melt that was geochemically similar to those forming fractionated, rare metal NYF pegmatites. The high Fe2O3 in feldspars and high Fe2O3/FeO in the dark mica, besides the presence of magnetite in the CAbG, suggests that it crystallized under relatively oxidizing conditions (-NINO). The CAbG shows very high contents of F, Na2O, Sn, Nb, Zr, U, Th, Zn, Li and Rb, and low CaO, MgO, TiO2, P2O5, Ba, and Sr. K/Rb and Rb/Sr ratios display extreme values, demonstrating the advanced fractionation of the liquid that originates the CAbG. The gullwing-shaped REE patterns and very low LaN/YbN ratios indicate the strong influence of F during magmatic evolution. The REE are distributed as M-type tetrads, showing that the fractionation mechanisms and the distribution of the REE's were controlled by processes similar to those observed in rare metal-bearing, evolved granitic systems. The Nd isotopes indicate crustal Paleoproterozoic protholiths for the two early facies of the Madeira Granite, which shows slightly negative εNd values. The CAbG and one sample of the hypersolvus grafite show low, positive εNd values. These data can be interpreted as indicating that: (1) the albite granite and the hypersolvus grafite have a protholith which is distinct from that of the earlier facies of the Madeira Granite; (2) both group of rocks derived from a same protholith but the Sm-Nd isotopic system of the albite granite and hypersolvus grafite was disturbed. Ali analyzed samples of the BAbG and an oxidized sample of the hypersolvus grafite shows strongly negative and scattered εNd values. This suggests that the hydrothermal processes that affected these rocks were able to strongly disturb their Nd isotopic system. The adopted petrogenetic nnodel, based on experiments on the system albite grafite -H20 - HF at 1 Kbar, suggests that the albite granite was originated from residual liquids derived from pristine F-rich, MgO-, TiO2--, CaO-depleted magmas. The very high F contents of the residual liquids strongly depressed the viscosity, density and the solidus of the system. This permitted a extreme fractionation of the melt, which evolved in a temperature interval coincident with those of pegmatitic processes. Due to the increase of the H2O contents in the residual liquid in the inner portions of the albite grafite, water saturation was attained and an aqueous fluids was segregated allowing the formation of pegmatitic rocks, while the F-rich residual melt phase generated the veins and pods of massive cryolite.